Numerical simulation of the dynamics and strucтure of a diffusion-driven flow on a wedge - Dimitrieva, Natalia Fedorovna; Chashechkin, Yuliy Dmitrievich (Computational Continuum Mechanics, 2015)
Generation of disturbances arising in a stratified medium due to the insertion of a wedge-shaped obstacle that breaks the homogeneity of a background diffusion flux and produces a complex system of slow flows is investigated. The fundamental equations of inhomogeneous multi-component fluid mechanics are used to describe the phenomena under consideration. In the present paper we propose a technique for modeling continuously modified fluids. The approach is implemented in the original OpenFOAM solvers. The computational domain is discretized using utilities blockMesh, topoSet and refineMesh of the OpenFOAM package, as well as an open source integration SALOME platform. A comparison of different methods for constructing effective high-resolution computational meshes for studying physical processes is carried out. High-resolution calculations are performed in a physically relevant parameter regime. Calculations are made in a parallel regime on the computational facilities of the web-laboratory UniHUB. ParaView and Origin packages are used for visualizing data. Calculation results demonstrate the efficiency of the proposed methods to model numerically diffusion-driven flows on a wedge in a stably stratified fluid. Numerical simulations are used to find the patterns of fields representing different physical quantities and to determine a difference in pressure between the vertex and base of the wedge that generates a propulsive force resulting in a self-motion of an obstacle along its neutral buoyancy horizon.